Accessory Cuboid Facet Associated with Calcaneonavicular Coalitions. Issue 1 (January 2022) - Scott, Daniel J.; Riccio, Anthony; Kanaan, Yassine; Zide, Jacob R.
Category: Hindfoot; Other Introduction/Purpose: Though resection and soft tissue interposition is the mainstay of surgical treatment for symptomatic calcaneonavicular coalitions (CNCs) that fail conservative treatment, some consternation exists as to balancing adequacy of resection with violation of adjacent talonavicular and calcaneocuboid (CC) articulations. As better understanding of nearby articular anatomy might be helpful in determining extent of resection, this study aims to identify differences in the anatomy of the CC articulation between feet with and without CNCs. Methods: A retrospective radiographic analysis of patients with symptomatic CNCs presenting to a single tertiary care pediatric hospital from 2010-2019 was performed. Patients without computed tomographic (CT) or magnetic resonance imaging (MRI) were excluded. Using either CT or MRI and standardized anatomic landmarks, the length and morphology of the calcaneal and cuboid articular surfaces were documented at the CC joint. When bilateral imaging was available in patients with a unilateral coalition, measurements were also made on the uninvolved side to provide a cohort of normal controls for comparison. Results: 81 CNCs in 55 patients were identified along with18 normal feet. Mean age was 11.7 years at the time of advanced imaging. In the coalition group, an accessory cuboid facet was identified articulating with the calcaneal portion of the coalition in 61/81 (75.3%) feet. The mean total length of the cuboid articular surface measured 28.6 mm (range, 22.4-34.9 mm). The average length of the accessory facet was 10.6 mm (range, 6.0-15.5 mm) while the length of the primary cuboid articulation with the calcaneus was 15.9 mm (range, 6.4-23.2 mm). Thus, the accessory facet comprised 37.2% of the cuboid articular surface in these patients. Patients without CNCs had a significantly larger primary cuboid articulation with the calcaneus of 21.6 mm (p<0.0001). An accessory cuboid facet was identified in only a single foot in the normal cohort. Conclusion: An accessory cuboid facet is present in over 75% of patients with CNCs and comprised nearly 40% of the proximal cuboid articular length. Moreover, significant differences in the shape of the cuboid portion of the CC joint were present in feet with and without CNCs. This information may be useful when planning the extent of CNC surgical resection as including the coalition side of the accessory articulation may have value in restoring hindfoot motion.